A study on the Development of Semurup Hot Spring Tourism Object at District of Air Hangat in Kerinci Regency - Anggia, Shinta (Sumatra Journal of Disaster, Geography and Geography Education, 2017)
This study aimed to investigate the physical and nonphysical characteristics, management and development strategies of Semurup or Spring tourism and to formulate policy directions of Semurup Hot Spring Tourism object development. The researcher combined to types of studies, qualitative and quantitative study (mixed method research) and used SWOT analysis and AHP analysis to analyze the data. The result of this research showed that (1) its physical characteristics (location, acessibility, attraction, amenity/facility) had met the criteria of tourism mentioned in The Regulation of Ministry of Public Workss number 41/Prt/M/2007 and its nonphysical characteristics (social-culture-economic and Sapta Pesona/sapta charm) did not yet give a positive impact on the development of Semurup Hot Spring tourism object (2) Management system of Semurup hot spring tourism object was directly managed by Government Tourism Office. (3) the development strategies were analyzed by SWOT analysis and there were eleven strategies which can be used to develop Semurup Hot Spring trousim object (4) policy direction of the development of Semurup Hot Spring tourism object by using AHP analysis. The result of AHP analysis revealed that there were five policy direction of Semutup Hot Spring tourism, namely: (a) promoting the tourism object (0.785), (b) the socialization about tourism awareness to improve local community’ knowledge of the tourism object (0.786), (c) involving the local comunity in the tourism management (0.779), (d) improving and increasing the facilties and infrastructure of Semurup hot spring tourism object (0.755), and (e) supporting local community’s creative economy activities (0.718).